Retail Banking in the Contemporary Financial Environment (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Which challenges does the retail banking industry face nowadays? Walking on the path of M. Porters theories, the author tries to open a window in the retail bankings present and future, the challenges the industry faces, the main forces that shape the competition, the strategies deployed in order to create a competitive advantage for the industry players, and a short prognosis for the industrys future